2022
DOI: 10.1155/2022/7030722
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Significance of microRNA-208a in Acute Myocardial Infarction

Abstract: Objective. To determine the prognostic and diagnostic significance of microRNA-208a (miR-208a) in acute myocardial infarction (AMI). Methods. Totally, 84 AMI patients hospitalized in our hospital between Jan. 2019 and Feb. 2021 were enrolled as the patient group (Pat group), and 50 healthy individuals over same time span as the control group (Con group). qRT-PCR assay was carried out to quantify serum miR-208a in the patients and receiver-operating characteristic (ROC) curves for analysing its diagnostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…This characteristic could potentially make them useful as biomarkers for timely diagnosis, staging, and monitoring of disease during treatment. For instance, multiple studies have shown that miR-208a in exosomes released from injured cardiomyocytes after MI has the advantages of strong myocardial specificity, high sensitivity and strong stability, and is positively correlated with the indexes of myocardial function before and after therapy [112,[179][180][181]. The functional diversity of exosomes secreted by cardiac cells also suggests that these various cell types should be further explored as potential sources of therapeutic exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic could potentially make them useful as biomarkers for timely diagnosis, staging, and monitoring of disease during treatment. For instance, multiple studies have shown that miR-208a in exosomes released from injured cardiomyocytes after MI has the advantages of strong myocardial specificity, high sensitivity and strong stability, and is positively correlated with the indexes of myocardial function before and after therapy [112,[179][180][181]. The functional diversity of exosomes secreted by cardiac cells also suggests that these various cell types should be further explored as potential sources of therapeutic exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests the potential of miR-208a as a promising biomarker for the diagnosis and prediction of AMI, thus positioning it as a highly valuable biomarker in clinical settings. [ 68 ] Multiple studies have shown that circulating miR-208 is a reliable biomarker for diagnosing STEMI and NSTEMI. Moreover, miR-208 can distinguish patients presenting with AMI symptoms, such as chest pain, from healthy controls.…”
Section: Emerging Biomarkers Associated With Amimentioning
confidence: 99%